Integrasi Algoritma Sosial Media dalam Mengoptimalkan Penggunaan Digital Marketing UMKM - Nela Safelia; Riski Hernando; Fitrini Mansur; Yenny Yuniarti; Erni Achmad; Fredy Olimsar; Shahri Bin Abu Seman (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
The International Community Service Program themed “Integration of Social Media Algorithms in Optimizing the Use of Digital Marketing for Micro and Small Enterprises (MSEs) in Indonesia and Malaysia” is a collaborative initiative between Universitas Jambi (UNJA) and Universiti Poly-Tech Malaysia (UPTM). This program aims to enhance the digital literacy capacity of micro-entrepreneurs through a comprehensive understanding of social media algorithms and the application of creative content strategies rooted in local wisdom and culture. The implementation methods include interactive training sessions, thematic workshops, intensive mentoring, and cross-country benchmarking to strengthen knowledge transfer and the adoption of best practices. The results demonstrate a significant improvement in participants’ digital competencies, reflected in their enhanced ability to optimize social media algorithms for product marketing, the establishment of a cross-border digitalpreneur community between Indonesia and Malaysia, and the development of adaptive digital marketing training modules and standard operating procedures (SOPs). The sustainability impact of this program not only increases the competitiveness and resilience of MSEs but also strengthens international academic collaboration between the two universities. Furthermore, this initiative contributes to achieving the universities’ Key Performance Indicators (KPI) and supports the development of an inclusive and sustainable digital economic ecosystem within the ASEAN region.